Analysis Of The VDI 2221 Method On Yarn Winding Tools - Ernest Alfie (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
UKM KF Kayra, based in Troso Village Rt 04/01, Pecangaan District, Jepara Regency, is a producer of ikat fabrics. Currently, the production process at UKM KF Kayra is still carried out manually. They implement a make to order production system. One of the obstacles faced is the weft thread winding process. Using a manual thread roller extends the process time, where one pallet can take 3 to 4 minutes. A thread winding operator can only produce about 100 pallets in one day, which is still not enough to meet the daily needs of weavers. Apart from that, operators who do milling also experience discomfort and injuries to their wrists and shoulders because the wheel turning process is done manually. Therefore, it is necessary to propose improvements by developing and redesigning existing tools, as well as making several improvements to increase productivity. In designing this thread winding tool, the VDI 2221 method was used, which is a systematic approach in the design of engineering systems and engineering products. The result of this design is a tool with an electric dynamo drive that rotates at 2800 rpm using a vbelt as the drive shaft for a pulley with a diameter of 2.5 inches. The analysis results from 10 tests show an average rolling time of 1.23 minutes per piece, which is more efficient than the previous tool which took 1.38 minutes. This new tool is not only more efficient in use, but also provides comfort and reduces the risk of injury for UKM KF Kayra employees.